The Effect of Agricultural Extension on The Level of Knowledge Among Rice Farmers In Kaloling Village, East Sinjai Subdistrict, Sinjai Regency - Ahfandi Ahmad; Megawati; Fadilah Nurdin; Nurhalyza; Risma Niswati Tarman (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2026)
This study aims to analyze the effects of extension intensity, extension materials, extension methods, and extension workers’ competencies on the knowledge levels of rice farmers. The study employed a quantitative approach using descriptive and associative (causal) research methods. Data were collected through a questionnaire distributed to 41 farmers selected using proportionate sampling, and then analyzed using multiple linear regression with the aid of SPSS version 26. The results of the study indicate that, individually, extension content (Sig. = 0.002) and extension methods (Sig. = 0.000) have a positive and significant effect on farmers’ knowledge levels, whereas extension intensity (Sig. = 0.109) and extension workers’ competence (Sig. = 0.266) do not have a significant effect. Simultaneously, all four variables had a significant effect on farmers’ knowledge levels, with an F-calculated value of 142.947 and a significance level of 0.000. The coefficient of determination (R²) value of 0.941 indicates that 94.1% of the variation in farmers’ knowledge levels can be explained by the research model, while 5.9% is influenced by other factors outside the model. The results of this study indicate that the quality of materials and the application of appropriate extension methods are key factors in improving rice farmers’ knowledge; therefore, these aspects require attention in the implementation of agricultural extension programs.